SINTESIS NANOPARTIKEL EKSTRAK KULIT BATANG TANAMAN KAYU JAWA (Lannea coromandelica) TERSALUT KITOSAN (bionature, 2022)
Extract of Kayu Jawa (Lannea coromandelica) bark plant is known to have biological activity, one of which is antibacterial. This research aimed to determine the inhibition of nanoparticles kayu jawa (Lannea coromandelica) bark against Stapylococcus aureus and Eschericia coli. The extraction of  Kayu Jawa (Lannea coromandelica) bark was carried out by maceration method using 70% ethanol as solvent. The extract of the Kayu Jawa (Lannea coromandelica) bark was synthesized to form chitosan-coated nanoparticles using the ionic gelation method and the results of the synthesis were characterized using X-Ray Difraction (XRD). The results showed that the synthesis of nanoparticles extract of Kayu Jawa (Lannea coromandelica) bark coated with chitosan had a particle size of 24.9 nm.